Nutritional Correlates of Human Oral Microbiome. (17th February 2017) - Kato, Ikuko; Vasquez, Adrian; Moyerbrailean, Gregory; Land, Susan; Djuric, Zora; Sun, Jun; Lin, Ho-Sheng; Ram, Jeffrey L.
Abstract : Background : Despite many potential effects of the oral microbiome on oral and systemic health, scant information is available regarding the associations between diet and the oral microbiome. Methods : Oral rinse DNA samples from 182 participants in a population-based case–control study for colorectal cancer were used to amplify a V3–V4 region of bacterial 16S rRNA gene. The amplicons were sequenced using Illumina MiSeq paired end chemistry on 2 runs, yielding approximately 33 million filtered reads that were assigned to bacterial classes. Relative abundances of each class and family as well microbial diversity/richness indices were correlated with selected dietary intakes from a food frequency questionnaire. Results : Saturated fatty acids (SFAs) and vitamin C intakes were consistently correlated with alpha (within-subjects) diversity indexes in both richness and diversity. SFA intake was positively correlated with relative abundance of betaproteobacteria and fusobacteria. Vitamin C and other vitamins with correlated intakes—for example, the B vitamins and vitamin E—exhibited positive correlations with fusobacteria class, its family Leptotrichiaceae and a clostridia family Lachnospiraceae. In addition, glycemic load was positively correlated with Lactobacillaceae abundance. Conclusion : The observed associations in this study were modest. However, the results suggest that the effects of diets are likely to be habitat specific, and observations from the gut microbiome are not transferrable to the oral microbiome. Further studies are warranted, incorporating a range of host biomarkers, such as cytohistological, molecular, or biochemical measurements, in order to address biological consequences of these dietary intakes in human oral health.